Pengujian Perangkat Lunak Aplikasi Studio Musik Nedd Audio Production Menggunakan Teknik Boundary Value Analysis - Fanni Sukma; Tri Lestari; Deddy Prayama; Dwiny Meidelfi; Danny Athaya (Teknik Elektro Politeknik Negeri Padang, 2021)
NEDD Audio Production is a recording studio that provides on-site music or track recording services and track sales. The owner still uses the manual system for scheduling records and still uses social media for track sales. This causes inefficient owner performance. To create a website that provides booking services for recording schedules and purchasing tracks that can help the owner in placing the recording schedule and purchasing tracks efficiently. The design used to create a website using UML (Unified Modeling Language), which consists of Use Case Diagrams.. Meanwhile, the programming language uses PHP and MySQL as a database. The implementation of this website uses a third-party service, namely Midtrans, which is a payment gateway service provider website from Indonesia